Miller-Keane encyclopedia & dictionary of medicine, nursing & allied health - Miller, Benjamin Frank, 1907-1971. 4 0 16; Keane, Claire Brackman; 5 (Philadelphia, Pennsylvania : W.B. Saunders Company, 1997)
Presents thousands of alphabetical entries covering medical as well as professional health care topics; also contains forty-five appendices and a floppy disk with which all the words in the book can be added to a WordPerfect or Microsoft Word spell checker.
Adult;Adult
Keywords: 2 -- 0; 6; Medicine;Nursing;Medicine;Nursing -- Dictionaries.;Dictionaries.;Dictionaries.;Dictionaries.; 20; 2